2008
DOI: 10.1038/cr.2008.71
|View full text |Cite
|
Sign up to set email alerts
|

Membrane glycoprotein M6A promotes μ-opioid receptor endocytosis and facilitates receptor sorting into the recycling pathway

Abstract: The interaction of μ-opioid receptor (MOPr) with the neuronal membrane glycoprotein M6a is known to facilitate MOPr endocytosis in human embryonic kidney 293 (HEK293) cells. To further study the role of M6a in the post-endocytotic sorting of MOPr, we investigated the agonist-induced co-internalization of MOPr and M6a and protein targeting after internalization in HEK293 cells that co-expressed HA-tagged MOPr and Myc-tagged M6a. We found that M6a, MOPr, and Rab 11, a marker for recycling endosomes, co-localized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 50 publications
1
26
0
Order By: Relevance
“…Thus, this domain might interact with some molecules responsible for the outgrowth arrest. Interestingly, a recent study reported that M6a binds to the seven-transmembrane l-opioid receptor via the transmembrane domains, and regulates distribution of these proteins onto the cell membrane surface (Wu et al, 2007;Liang et al, 2008), suggesting a general implication of M6a for recruitment and scaffolding function. Identifying M6a interactors on the growth cone edge may pave the way for understanding the unique axon behavior induced by the anti-M6a mAbs.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, this domain might interact with some molecules responsible for the outgrowth arrest. Interestingly, a recent study reported that M6a binds to the seven-transmembrane l-opioid receptor via the transmembrane domains, and regulates distribution of these proteins onto the cell membrane surface (Wu et al, 2007;Liang et al, 2008), suggesting a general implication of M6a for recruitment and scaffolding function. Identifying M6a interactors on the growth cone edge may pave the way for understanding the unique axon behavior induced by the anti-M6a mAbs.…”
Section: Discussionmentioning
confidence: 97%
“…The next category of DOPr-interacting proteins corresponds to those involved in receptor desensitization and trafficking. Some of these proteins, such as GRKs and barrs, interact with the receptor after its stimulation (see sections VII.A and VII.B for details), whereas others like GASPs Simonin et al, 2004) and glycoprotein M6a (Wu et al, 2007;Liang et al, 2008) associate constitutively (Fig. 2).…”
Section: D-opioid Receptor Pharmacologymentioning
confidence: 99%
“…Glycoprotein M6a is a membrane protein with four TMHs, two of which (the third and fourth) directly interact with TMH4, TMH5, and TMH6 of the receptor (Wu et al, 2007). M6a overexpression was shown to redirect DOPr to the recycling path (Liang et al, 2008), but it is not yet known whether it has this same effect at endogenous expression levels. NHERF also interacts with DOPr, although with much lower affinity than KOPr (Huang et al, 2004).…”
Section: D-opioid Receptor Pharmacologymentioning
confidence: 99%
“…Among them, we can acknowledge their potential involvement in membrane dynamics. More specifically, heterologous expression analyses have shown that M6a and M6b affect membrane trafficking and cell surface expression of G protein-coupled receptors such as the μ-opioid receptor and the serotonin transporter [21], [22], [23]. As the most abundant protein in the myelin membrane, PLP/DM20 is synthesized by oligodendrocytes, regulates the regularly-spaced apposition of myelin membranes, and maintains their stability [24], [25], [26].…”
Section: Introductionmentioning
confidence: 99%